THE EFFECT OF HOUSEHOLD INCOME AND CONSUMPTION LEVEL ON THE WELFARE OF FLOWER FARMING FAMILY IN TOMOHON CITY - Tumangkeng , Steeva Y. L.; Untu, Victoria Neisye; Moniharapon, Silcyljeova (International Journal of Research -GRANTHAALAYAH, 2022)
Family welfare is one indicator of the economic progress of a region. This is important because if people’s welfare increases, it will automatically increase economic growth. A person can be said to be prosperous if he can fulfill his physical and spiritual needs and development. This study aims to determine and analyze the extent of the influence of household income and consumption on the welfare of flower farming families in the city of Tomohon. This research is a quantitative descriptive research using multiple linear regression analysis method. The output of this research is in the form of a study of how the influence of income levels and household consumption on the welfare of flower farmer families in Tomohon City, besides that, the output of this research is the publication of International Journals and Intellectual Property Rights.